Neutron-Gamma Pulse Shape Discrimination with a NE-213 Liquid Scintillator by Using Digital Signal Processing Combined with Similarity Method - Mardiyanto Mardiyanto (PPIKSN-BATAN, 2008)
Neutron-Gamma Pulse Shape Discrimination with a NE-213 Liquid Scintillator by Using Digital Signal Processing Combined with Similarity Method. Measurement of mixed neutron-gamma radiation is difficult because a neuclear detector is usually sensitive to both radiations. A new attempt of neutron-gamma pulse shape discrimination for a NE-213 liquid scintillator is presented by using digital signal processing combined with an off-line similarity method. The output pulse shapes are digitized with a high speed digital oscilloscope. The n-γ discrimination is done by calculating the index of each pulse shape, which is determined by the similarity method, and then fusing it with its corresponding pulse height. Preliminary results demonstrate good separation of neutron and gamma-ray signals from a NE-213 scintillator with a simple digital system. The results were better than those with a conventional rise time method. Figure of Merit is used to determine the quality of discrimination. The figure of merit of the discrimination using digital signal processing combined with of line similarity method are 1.9; 1.7; 1.1; 1.1; and 0.8 ; on the other hand by using conventional method the rise time are 0.9; 0.9; 0.9; 0.7; and 0.4 for the equivalent electron energy of 800 ; 278 ; 139 ; 69 ; and 30 keV.